2021
DOI: 10.48550/arxiv.2103.12737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinematics beats dust: unveiling nested substructure in the perturbed outer disc of the Milky Way

Chervin F. P. Laporte,
Sergey E. Koposov,
Vasily Belokurov

Abstract: We use the Gaia eDR3 data and legacy spectroscopic surveys to map the Milky Way disc substructure towards the Galactic Anticenter at heliocentric distances d ≥ 10 kpc. We report the discovery of multiple previously undetected new filaments embedded in the outer disc in highly extincted regions. Stars in these over-densities have distance gradients expected for disc material and move on disc-like orbits with v φ ∼ 170 − 230 km s −1 , showing small spreads in energy. Such a morphology argues against a quiescentl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kazantzidis et al 2009;Gómez et al 2017) which is also becoming increasingly accessible to observed data sets (e.g. Gaia Collaboration et al 2021;Laporte et al 2021). Due to the longer orbital timescales in the outer disc, older excited structures from prior interactions can remain coherent to the present-day.…”
Section: Modelmentioning
confidence: 99%
“…Kazantzidis et al 2009;Gómez et al 2017) which is also becoming increasingly accessible to observed data sets (e.g. Gaia Collaboration et al 2021;Laporte et al 2021). Due to the longer orbital timescales in the outer disc, older excited structures from prior interactions can remain coherent to the present-day.…”
Section: Modelmentioning
confidence: 99%
“…In addition, as part of the science verification of the Gaia early third data release (Gaia EDR3), Gaia Collaboration et al (2021a) revealed the complex structure of the disc towards the anticentre with, among others, the detection of velocity oscillations throughout the plane, and the identification of stellar overdensities associated to Monoceros, TriAnd, and the anticentre stream. Further structures have been detected recently in Laporte et al (2021) also using this approximation.…”
Section: Introductionmentioning
confidence: 62%